2021
DOI: 10.47391/jpma.015
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ attitudes towards the clinical importance of embryology

Abstract: Objective of study: The objective of the study is to identify the attitudes of medical students towards the clinical importance of embryology. Methodology: The cross-sectional questionnaire-based survey was conducted at a private medical college of Sialkot, Islam Medical College from September 2019 to November 2019. Ethical approval was obtained from the Institutional Research and Ethics Committee prior to the study. Hundred First year and 100 final year medical students of Islam Medical College, participated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…The majority of students in this study had a favorable attitude towards embryology and recognized that it as an essential instrument in the eld of medicine. This is similar to recent studies conducted by Sume et al (2022) in Ethiopia ( 14), Waseem et al (2021) in Pakistan (13), and Zaletel et al (2016) in Serbia (18). All of these studies found that medical students recognizes and value the signi cance of embryology.…”
Section: Discussionsupporting
confidence: 92%
“…The majority of students in this study had a favorable attitude towards embryology and recognized that it as an essential instrument in the eld of medicine. This is similar to recent studies conducted by Sume et al (2022) in Ethiopia ( 14), Waseem et al (2021) in Pakistan (13), and Zaletel et al (2016) in Serbia (18). All of these studies found that medical students recognizes and value the signi cance of embryology.…”
Section: Discussionsupporting
confidence: 92%
“…By means of a large‐scale survey, Moxham et al (2017) reported that medical students across Europe considered histology to be an important, and relevant, part of their medical training. A similar finding, using similar methodologies, has been reported by Waseem et al (2021) for medical students in Pakistan. This accords with the attitudes of laypersons in Europe who consider that the anatomical sciences are highly clinically relevant.…”
Section: Discussionsupporting
confidence: 89%
“…Medical students should be encouraged to take ownership of their own clinical learning by adopting a variety of attitudes and behaviors that can enrich their educational experience, facilitate teaching from residents and faculty, and promote a positive learning environment (9). Although there are studies on anatomy (10), embryology (11), pathology (12), psychiatry (13), nephrology (14) and neurology (15) courses that evaluate student attitudes in medical education, there is no study that develops an attitude scale in the field of pharmacology. In a limited number of studies related to the pharmacology course, attitude towards different evaluation methods (16), correlation between attendance of lectures and exam performance (17), and impact of teambased learning on student satisfaction and performance (18) were evaluated.…”
Section: Introductionmentioning
confidence: 99%